Wireless Acoustic Low-cost Sensor Network for Urban Noise Monitoring - Simona Domazetovska, Maja Anachkova, Viktor Gavriloski, Zlatko Petreski (Forum Acusticum, 2020)
The concept of low-cost sensor network based on Internet of Things (IoT) technology for monitoring environmental parameters is trendy area of research that has attracted a lot of scientific attention recently. Amongst the several pollutant that have to be faced on a daily basis, the noise pollution is one of the most widely known emerging and challenging problem in all large metropolitan areas, affecting the health of citizens in multiple ways. Recent technologies of low-cost and low-power devices allowed researchers to develop monitoring Wireless Sensor Units (WSUs) with wireless network for providing higher granularity than the traditional hand-held analyzers, allowing massive noise monitoring. This paper presents prototyping of low-cost WSUs based on chosen sensor with different network platforms for noise monitoring and analysis. The units aim to measure the equivalent noise level in dB(A) and provide continuous and autonomous data acquisition. The accuracy of the WSUs are configured by comparing the results with professional hand-held analyzer through laboratory and outdoor evaluation test. This evaluation has shown the devices as powerful and affordable low-cost units able to publish results online that could help in increasing the population awareness for the noise.
Keywords: Urban Noise, Wireless Sensor Units, Low-cost Sensor Network, Noise Monitoring